Behavioral Aspects in Accountability Accounting and Their Influence on Performance Achievement - Wawan Anggara; Firmansyah (www.amertainstitute.com, 2024)
This study aims to examine the influence of behavioral aspects, such as motivation, job satisfaction, organizational commitment, and perception of fairness, on performance achievement in the context of accountability accounting. Accountability accounting is a system that emphasizes the accountability of each work unit in achieving organizational targets, and its success is greatly influenced by behavioral factors that exist in the organization. Using quantitative methods and data obtained from questionnaires to company employees, this study analyzes the relationship between behavioral aspects and performance achievement. The results showed that motivation, job satisfaction, organizational commitment, and perception of fairness had a positive and significant influence on performance improvement. These findings indicate that an effective accountability accounting system not only depends on technical procedures, but also requires an approach that takes into account the psychological and social factors of employees. This research makes an important contribution to company management in designing policies that support employee welfare and improve accountability and achievement of organizational performance.